2022
DOI: 10.1086/714592
|View full text |Cite
|
Sign up to set email alerts
|

Business Training and Mentoring: Experimental Evidence from Women-Owned Microenterprises in Ethiopia

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Also looking at Kenya, McKenzie and Puerto (2021) found that mentorship did not increase the effects of the gender-oriented business training offered. Bakhtiar et al (2022) found that a mentorship program in Ethiopia did not significantly increase the profits of the mentees, but mentoring improved the business performance of the women entrepreneurs who functioned as mentors.…”
Section: Personalized Services Through Mentorship and Consultingmentioning
confidence: 93%
“…Also looking at Kenya, McKenzie and Puerto (2021) found that mentorship did not increase the effects of the gender-oriented business training offered. Bakhtiar et al (2022) found that a mentorship program in Ethiopia did not significantly increase the profits of the mentees, but mentoring improved the business performance of the women entrepreneurs who functioned as mentors.…”
Section: Personalized Services Through Mentorship and Consultingmentioning
confidence: 93%
“…Microenterprises including those of women underperform and have a higher exit rate than other forms of businesses in developing economies (Bakhtiar et al , 2022). Maintaining and growing their businesses beyond start-up is a serious challenge for these women in Ghana.…”
Section: Theoretical Backgroundmentioning
confidence: 99%